Two-dimensional speckle tracking echocardiography: standardization efforts based on synthetic ultrasound data. (18th August 2015) - D'hooge, Jan; Barbosa, Daniel; Gao, Hang; Claus, Piet; Prater, David; Hamilton, Jamie; Lysyansky, Peter; Abe, Yasuhiko; Ito, Yasuhiro; Houle, Helene; Pedri, Stefano; Baumann, Rolf; et al.
Abstract: Aims: Speckle tracking echocardiography has already demonstrated its clinical potential. However, its use in routine practice is jeopardized by recent reports on high inter-vendor variability of the measurements. As such, the European Association of CardioVascular Imaging (EACVI) and the American Society of Echocardiography (ASE) set up a standardization task force, which was joined by all manufacturers of echocardiographic equipment as well as by companies offering software solutions only, with the ambition to tackle this problem by standardization and quality assurance (QA). Methods and results: In this study, a first step towards QA of all commercially available tracking solutions based on computer-generated ultrasound images is presented. The accuracy of the products was acceptable with relative errors below 10% and intra-vendor reproducibility within 5%. Conclusion: Whether these results can be extrapolated to the clinical setting is the topic of an ongoing study of the EACVI/ASE/Industry Task Force to standardize deformation imaging. This study was an important first step in the development of generally accepted tools for QA of speckle tracking echocardiography.